Understanding Factors Associated With Motivation To Quit Vaping Among Vapers In The Federal Territory Of Kuala Lumpur, Malaysia - Lei Hum Wee; Jo Ann Andoy Galvan; Sapna Shridhar Patil; Priya Madhavan; Dinesh Mahalingam; Chai Hong Yeong; Yin How Wong; Hui Qi Poh; Sanjay Suthahar; Shamella Diya David; Xiao Jing Tan; Izzah Athirah Rosli; et al. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Indexed by WOS/ Scopus